2015
DOI: 10.24925/turjaf.v3i6.466-471.340
|View full text |Cite
|
Sign up to set email alerts
|

A Research on Red Meat Consumption and Preferences: A Case Study in Tekirdağ Province

Abstract: In this study, 384 persons have been subjected to questionnaire made in order to determine the red meat consumption and preferences of the people living in the central district of Tekirdağ province. In the study it was determined that all the consumers consumed red meat. According to the findings of the research, the annual red meat consumption per capita was determined to be 34.22 kg. Considering the red meat consumption of the people subjected to research, it was determined that beef meat was the most prefer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…This result also supports the findings of Harper and Makatouni (2002), Verbeke et al (2005) and Baker et al (2002). Turkish consumers generally prefer red meat because they believe it is healthy, delicious and convenient (Onurlubas et al, 2015). Consumers need assurance regarding the healthiness of meat, and this assurance could improve trust toward meat products.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…This result also supports the findings of Harper and Makatouni (2002), Verbeke et al (2005) and Baker et al (2002). Turkish consumers generally prefer red meat because they believe it is healthy, delicious and convenient (Onurlubas et al, 2015). Consumers need assurance regarding the healthiness of meat, and this assurance could improve trust toward meat products.…”
Section: Discussionsupporting
confidence: 85%
“…A research study conducted by consulting more than 2,500 households in Turkey revealed that income significantly influences meat consumption (Sacli and Ozer, 2017). In another study, 75 percent of the participants stated that they would increase their meat consumption if the price level of meat were reduced (Onurlubas et al, 2015). Regarding sustainability issues, economic concerns such as the high price of meat have superseded the possible sustainability gains of meat curtailment.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that the frequency of eating fast food by young adults aged 18-30 was directly related to weight gain or an increase in weight (Dahm et al, 2010). Onurlubaş and Yılmaz (2013) found in their study that more than 90% of participants consider fast food to be unhealthy. Furthermore, when asked about the harmful effects of fast food, 80.8% of participants cited obesity, 72.8% cited cardiovascular problems, and 57.7% cited high cholesterol.…”
Section: Introductionmentioning
confidence: 94%
“…In other words, "value is affordable quality." (Zeithaml, 1988, 13) Similarly, Onurlubaş and Yılmaz (2013) find that the most frequently mentioned factor as a cause for university students to prefer fast food is the price-quality relationship.…”
Section: Introductionmentioning
confidence: 99%
“…These habits include irregular meals, frequent snacking, eating away from home, and adopting alternative dietary patterns, all of which characterize the food habits of young adults stemming from adolescence [7,12]. mentioned that eating fast foods for meals or snacks is especially popular with young adults [8,13]. During early adulthood, many changes begin that lead to the development of diseases of aging several years later [9,14].…”
Section: Introductionmentioning
confidence: 99%